The micro and nano scale characterization and identification of tablet formulations - Jin, Zheng (2010)
The aim of this project was to characterize the surface properties of materials used in tablet formulations with sub-micron resolution by the techniques of Atomic Force Microscopy (AFM), Scanning Electron Microscopy (SEM), Scanning Thermal Microscopy (SThM), Nano-TA system, Differential Scanning Calorimeter (DSC), Attenuated Total Reflectance Infrared (ATR-IR), Near-Infrared Spectroscopy (NIR) and Time-of-Flight Secondary Ion Mass Spectrometry (ToF-SIMS). In particular, the work aimed to develop new AFM based methodologies to advance this method both in terms of quantification and mapping. AFM was employed to investigate properties of solid materials such as surface free energy, Young’s modulus, melting point and phase transition temperatures from pharmaceutical materials in blend mixtures with the nanoscale resolution. These approaches developed here provide new tools to understand the process induced changes and stability issues in solid dosage forms such as tablets and inhalation formulations from minute amounts of materials.